MicroRNA-429/Cxcl1 Axis Protective Against Oxygen Glucose Deprivation/Reoxygenation-Induced Injury in Brain Microvascular Endothelial Cells - Jun Leng; Wei Liu; Li Li; Fang Yue Wei; Meng Tian; Hui Min Liu; Wen Guo (SAGE Publishing, 2020)
Objective: The objective of the present work was to study the role of Cxcl1 in cerebral ischemia-reperfusion (I/R) injury and to in-depth explore its pathogenesis. Methods: The expression of Cxcl1 based on the public data was analyzed. Then, we constructed an oxygen glucose deprivation/reoxygenation (OGD/R) model in vitro using mice brain microvascular endothelial cells (BMECs) to simulate cerebral I/R in vivo. Results: The results of quantitative real-time polymerase chain reaction assay uncovered that Cxcl1 showed higher expression while miR-429 showed lower expression in BMECs damaged by OGD/R, whereas overexpression of Cxcl1 or inhibition of miR-429 expression can strengthen this effect. Hereafter, through dual luciferase reporter assay, we verified that miR-429 directly targets Cxcl1 and negatively regulates Cxcl1 expression. Furthermore, the results also revealed that overexpression of Cxcl1 can reverse the miR-429-mediated effects. Conclusion: We concluded that miR-429 exerts protective effects against OGD/R-induce injury in vitro through modulation of Cxcl1 and nuclear factor kinase B pathway, hoping provide a new view on the pathogenesis of cerebral I/R injury and a feasible potential therapeutic target.